Report of a Novel Bilateral Variation of Sciatic and Inferior Gluteal Nerve: A Case Study - Rahim Golmohammadi; Ali Delbari (Basic and Clinical Neuroscience, 2021)
Introduction: The sciatic nerve is the thickest nerve of the sacral plexus which innervates many muscles and vast areas of the skin of the lower limb. It leaves the pelvis via the greater sciatic foramen, emerges into the gluteal region by passing under the piriformis muscle, and descends beneath the gluteus maximus to divide into its terminal branches; the tibial and common peroneal nerve at the superior angle of the popliteal fossa. In some cases, the sciatic nerve divides into the tibial and common peroneal nerves at a higher level and one of them or both passes through or over the piriformis muscle. Case Presentation: We find an interesting bilateral variation of sciatic nerve accompanying a very thick inferior gluteal nerve on the right side and unusual route and branching of tibial and common peroneal nerves on the left side. Conclusion: As in conditions like intramuscular injections, gluteal surgeries, and piriformis syndrome such variations may increase the risk of injury, it is important for the medical team to be aware of them. In this paper, by reporting many variations in a cadaver, we emphasize the importance of anatomical variations, especially for surgeons and nurses.